A conceptual model to understand the correlation between topography and wetting of polypropylene- and polyethylene-based wood–plastic composites. (August 2016) - Calvimontes, Alfredo; Bellmann, Cornelia; Schirp, Claudia; Schirp, Arne
Microscopic and physico-chemical methods were used for a comprehensive surface characterization of different extruded polypropylene- and polyethylene-based wood–plastic composite (WPC) formulations. The surfaces were analysed using stereophotogrammetry, high-resolution scandisk confocal microscopy and scanning electron microscopy, resulting in detailed information about the topography and surface morphology. In addition, dynamic water contact angle measurements were carried out to characterize the wettability of the samples. The effects of polymer type, polymer content, additive content and processing method on the resulting topography and wetting were investigated. The correlation between topography and wetting resulted in a conceptual model of WPC surface morphology and wetting, which may be applied to optimize adhesion properties of this composite material.